2009
DOI: 10.1086/596710
|View full text |Cite
|
Sign up to set email alerts
|

Detection of CirculatingChlamydophila pneumoniaein Patients with Coronary Artery Disease and Healthy Control Subjects

Abstract: The uniformly negative results with use of highly sensitive methods are in contrast to much of the published literature. Probing of PBMCs for the genes of C. pneumoniae does not appear useful as a noninvasive way of detecting the presence of C. pneumoniae in atheromatous lesions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
15
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 35 publications
1
15
0
Order By: Relevance
“…The prevalence of DNA detection varied between 0 to 100% in arteries 2 and 0 to 86% in blood leukocytes. 4,7 In most of these studies, PCR was performed by methods that could amplify non-C. pneumoniae DNA: RT-PCR could minimize this risk. 10 Our study confirms previous results in non-diabetic subjects 7 .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The prevalence of DNA detection varied between 0 to 100% in arteries 2 and 0 to 86% in blood leukocytes. 4,7 In most of these studies, PCR was performed by methods that could amplify non-C. pneumoniae DNA: RT-PCR could minimize this risk. 10 Our study confirms previous results in non-diabetic subjects 7 .…”
Section: Discussionmentioning
confidence: 99%
“…3 Using polymerase chain reaction (PCR), both the absence and presence of C. pneumoniae-DNA in atherosclerotic plaques or blood leukocytes has been reported. 4,5 However, most studies used nested PCR, yielding a high rate of false positive results. 6 Recently, no C. pneumoniae-DNA was found using a probe-based real-time PCR (RT-PCR) in leukocytes from patients with atherosclerotic plaques 7 or coronary artery disease.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Seroepidemiological studies indicate that C. pneumoniae infection is by far the most common human chlamydial infection in different cohorts, with seropositivity in at least 50% of the general population over age 20 [4][5][6][7][8][9][10]. But PCR studies on asymptomatic healthy adults (more than 1000) had established only 1% of positivity in nasopharyngeal swabs specimens [11] In addition to pneumonia, pharyngitis, bronchitis and asthma C. pneumonia is also associated with arteriosclerosis, lung cancer, multiple sclerosis and Alzheimer's disease [12][13][14][15][16][17][18] C. pneumoniae can infect, reside and replicate in various cells types including smooth muscle cells, fibroblasts, endothelial cells, bronchial epithelial cells, keratinocytes as well as various immune cells such as macrophages, lymphocytes and natural killers cells (NK) [19,20] It induces the increased release of pro-inflammatory mediators including tumor necrosis factor alpha (TNF-α), interleukin 6 and 8 (IL-6, IL-8), basic fibroblast growth factor (bFGF) and up regulates adhesion molecules [21]. Recently it has been suggested that C. pneumoniae infection may also stimulate the IL-10 production which down regulates the expression of major histocompatibility complex class I (MHC-I), inhibits apoptosis and increases the longevity of the host cell, enhancing the survival of bacteria itself [22,23].…”
Section: Introductionmentioning
confidence: 99%
“…C. pneumoniae can infect immune cells including monocyte/macrophages in vitro [6]. In addition, in several studies, C. pneumoniae DNA has been detected in peripheral blood mononuclear cells from patients with cardiovascular disease and from blood donors [7,8], but not in others [9]. It is possible that C. pneumoniae uses monocytes as a means of transport from the initial site of infection to other anatomical locations in which persistent infection can be established and chronic inflammatory disease ensues.…”
Section: Introductionmentioning
confidence: 99%